Determinants of Customer Revisit Intention as a Driver of Microeconomic Development : VT House Billiard Case - Pungus, Toar; Berlianto, Margaretha Pink (Yayasan Riset dan Pengembangan Intelektual, 2025)
The sports and recreation industry plays an important role in supporting microeconomic development by generating local business growth and employment opportunities. Billiard facilities, such as VT House Billiard, contribute to this sector by providing a venue for skill development and leisure activities. This study investigates the determinants of customer revisit intention and their broader implications for microeconomic development in the local community. Specifically, it examines how perceived price, service quality, positive emotional experience, and store atmosphere influence customer satisfaction, which in turn affects electronic word of mouth (e-WOM) and revisit intention among VT House Billiard visitors. Data were collected from 259 customers and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that all proposed factors positively impact customer satisfaction, which significantly drives both e-WOM and the intention to revisit. These results suggest that enhancing customer experience not only benefits business sustainability but also contributes to the microeconomic growth of the local area through increased patronage and community engagement.